High performance drive control for electric vehicle - See, Yi Teik (Nanyang Technological University, 2022)
With global warming becoming a world scale concern, many countries have therefore pledged for carbon neutrality, looking for ways to on reducing carbon emissions, with the implementation of Electric Vehicles being one of such major considerations.